PENTINGNYA PENDIDIKAN MULTIKULTURAL DAN PENDIDIKAN INKLUSI DI SEKOLAH DASAR DALAM MENGHARGAI KEBERAGAMAN : STUDI LITERATUR - Tri Handayani, Puji; Zakiah, Linda; Maulida, Nadra; Salsabillah Zahra, Ananda; Jaya, Indra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to discuss the importance of multicultural education and inclusion in primary schools in the context of Indonesia's diversity. With a large population and abundant cultural wealth, Indonesia is the largest multicultural country in the world. However, there are still challenges in implementing multicultural and inclusive education, especially related to violence in the school environment which is often triggered by students' lack of understanding of the meaning of multiculturalism and inclusion. Lack of multicultural education, inclusion, and awareness of the importance of respecting diversity are the main causes of violence in elementary schools. Multicultural and inclusive education is expected to shape students' character to accept, appreciate, and respect differences and avoid discrimination as well as the importance of creating a safe, inclusive, and respectful learning environment.